AN ANALYSIS OF ENGLISH-INDONESIAN SUBTITILING PROCEDURES OF THE MOVIE ENTITLED "INTO THE WILD" - Kania, Anken Nur (2014)
Penelitian ini ditujukan untuk mengetahui prosedur penerjemahan dan menganalisis kualitas dari penerjemahan subtitle dalam film "Into the Wild". Studi kasus kualitatif digunakan sebagai metode dalam pengumpulan data. Dalam proses pengumpulan data, 300 kalimat di subtitle pada film dipilih dengan menggunakan metode sampling interval sebagai sampel untuk dianalisis dan tiga orang yang berpengalaman dalam penerjemahan diminta untuk menilai kualitas penerjemahan subtitle. Hasilnya dibandingkan dengan penilaian dari peneliti berdasarkan teori kualitas penerjemahan yang baik oleh Larson (1998), Nida, Lewis, dan Leonard Foster (1958) dalam Venutti (2000), Newmark (1988), Tytler (1979) dalam Munday (2001), Benjamin (1969/2000) dalam Munday (2001), dan Massoud (1988) dan El Shafey (1985) dalam Abdellah (2005). Hasil penelitian menunjukkan bahwa ada sembilan prosedur penerjemahan yang digunakan di subtitle pada film berdasarkan teori Newmark (1988), Vinay dan Darbelnet (2000) dalam Munday (2001), Dryden dalam Munday (2001), Catford (1965) dalam Munday (2001), Delisle, Lee-Jahnke & Cormier (1999), dan Harvey (2003), yaitu: literal, transference, cultural equivalent, shift, compensation, reduction and expansion, paraphrase, kombinasi prosedur seperti couplets, triplets, dan quadruplets, dan beberapa kalimat yang tidak diterjemahkan. Peneliti dan tiga orang yang berpengalaman dalam penerjemahan menilai bahwa subtitle pada film "Into the Wild" berkualitas dan memenuhi kriteria penerjemahan yang baik. Berdasarkan hasil penelitian, studi selanjutnya mengenai penerjemahan subtitle pada film diharapkan untuk melakukan analisis yang lebih mendalam mengenai prosedur dan kualitas penerjemahannya. Kata kunci: Penerjemahan, Penerjemahan Subtitle, Prosedur Penerjemahan, Kualitas Penerjemahan. This study was aimed at finding out the English-Indonesian subtitle translation procedures and analyzing the quality of its translation. A qualitative case study was used as a conceptual framework for collecting the data. In order to systematically conduct the study, 300 sentences of the film subtitle were selected by using sampling interval method as the sample to analyze and three persons who are experienced in translation field were asked to judge the quality of English-Indonesian subtitle translation. It was compared with the researcher judgment based on the good translation theories from some experts, such as Larson (1998), Nida, Lewis, and Leonard Foster (1958) in Venutti (2000), Newmark (1988), Tytler (1979) in Munday (2001), Benjamin (1969/2000) in Munday (2001), and Massoud (1988) and El Shafey (1985) in Abdellah (2005). The findings obtained from the analysis show that there are nine translation procedures used in the film subtitle based on Newmark (1988), Vinay and Darbelnet (2000) in Munday (2001), Dryden in Munday (2001), Catford (1965) in Munday (2001), Delisle, Lee-Jahnke & Cormier (1999), and Harvey (2003) theories, those are: literal, transference, cultural equivalent, shift, compensation, reduction and expansion, paraphrase, the combination of procedures, such as couplets, triplets, and quadruplets, and some untranslated sentences. Then, the English-Indonesian film subtitle that has already been judged by the researcher and by the three persons who are experienced in translation field was qualified and fulfilled the criteria of good translation. Finally, from the result of the research, the further study about subtitle translation is expected to conduct more comprehensive analysis of its translation procedures and quality. Keywords: Translation, Subtitle Translation, Translation Procedure, Translation Quality